PET Tau Imaging and Motor Impairments Differ Between Corticobasal Syndrome and Progressive Supranuclear Palsy With and Without Alzheimer's Disease Biomarkers - Vasilevskaya, Anna; Taghdiri, Foad; Multani, Namita; Anor, Cassandra; Misquitta, Karen; Houle, Sylvain; Burke, Charles; Tang-Wai, David; Lang, Anthony E.; Fox, Susan; Slow, Elizabeth; Rusjan, Pablo; et al. (Frontiers in Neurology, 2020)
Introduction: Frontotemporal lobar degeneration (FTLD)-related syndrome includes Progressive supranuclear palsy (PSP) and Corticobasal syndrome (CBS). PSP is usually caused by a tauopathy but can have associated Alzheimer’s disease (AD) while CBS can be caused by tauopathy, transactive response DNA binding protein 43 kDa or AD pathology. Our aim was to compare the parkinsonian syndromes presenting without AD biomarkers (CBS/PSP-non-AD) to parkinsonian syndromes with AD biomarkers (CBS/PSP-AD). Materials & Methods: Twenty-four patients [11 males, 13 females; age (68.46±7.23)] were recruited for this study. The whole cohort was divided into parkinsonian syndromes without AD biomarkers [N=17; diagnoses (6 CBS, 11 PSP)], and parkinsonian syndromes with AD biomarkers [N=7; diagnoses (6 CBS-AD, 1 PSP-AD)]. Anatomical MRI and PET imaging with tau ligand [18F]-AV1451 tracer was completed. Cerebrospinal fluid analysis or [18F]-AV1451 PET imaging was used to assess for the presence of AD biomarkers. Progressive supranuclear palsy rating scale (PSPRS) and unified Parkinson’s disease rating scale (UPDRS) motor exam were implemented to assess for motor disturbances. Language and cognitive testing were completed. Results: The CBS/PSP-non-AD group [age (70.18±6.65)] was significantly older (p=0.028) than CBS/PSP-AD group [age (64.29±7.32)]. There were no differences between the groups in terms of gender, education, years of disease duration, and disease severity as measured with the Clinical Dementia Rating scale. The CBS/PSP-non-AD group had significantly lower PET Tau Standard Volume Uptake Ratio (SUVR) values compared to the CBS/PSP-AD group in multiple frontal and temporal areas, and inferior parietal (all p<0.03). The CBS/PSP-non-AD group had significantly higher scores compared to CBS/PSP-AD group on PSPRS (p=0.004) and UPDRS motor exam (p=0.045). The CBS/PSP-non-AD group had higher volumes of inferior parietal, precuneus, and hippocampus (all p<0.02); but lower volume of midbrain (p=0.02), compared to the CBS/PSP-AD group. Discussion: The CBS/PSP-non-AD group had higher motor disturbances compared to the CBS/PSP-AD group, however both groups performed similarly on neuropsychological measures. The AD biomarker group had increased global uptake of PET Tau SUVR and lower volumes in AD-specific areas. These results show that the presenting phenotype of CBS and PSP syndromes and the distribution of injury are strongly affected by the presence of AD biomarkers.